2004
DOI: 10.1038/oby.2004.135
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Alters Respiratory Gas Exchange and Nutrient Metabolism in Type 2 Diabetic Rats

Abstract: HARADA, NAGAKATSU, CHIKA NINOMIYA, YOSHIE OSAKO, MASAKI MORISHIMA, KAZUAKI MAWATARI, AKIRA TAKAHASHI, AND YUTAKA NAKAYA. Taurine alters respiratory gas exchange and nutrient metabolism in type 2 diabetic rats. Obes Res. 2004; 12:1077-1084. Objective: To assess the effect of taurine supplementation on respiratory gas exchange, which might reflect the improved metabolism of glucose and/or lipid in the type 2 diabetic Otsuka Long-Evans Tokushima Fatty (OLETF) rats. Research Methods and Procedures:Male OLETF rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…2B). This effect of taurine treatment is in agreement with some rodent studies that showed taurine administration attenuated the increase of blood glucose concentration during glucose tolerance testing [11][12][13][14][15][16][17] . In general, most glucose (>80%) is taken up by skeletal muscle 21) .…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…2B). This effect of taurine treatment is in agreement with some rodent studies that showed taurine administration attenuated the increase of blood glucose concentration during glucose tolerance testing [11][12][13][14][15][16][17] . In general, most glucose (>80%) is taken up by skeletal muscle 21) .…”
Section: Discussionsupporting
confidence: 76%
“…Although we should consider that there are possibilities that taurine admin- treatment is stimulation of insulin secretion. Some studies demonstrated that taurine administration improved glucose tolerance in rodents without altering the plasma insulin concentration 11,13) ; whereas others reported that taurine administration increased insulin secretion from islets 14,16,17) . In our experiment, no significant difference was observed in the plasma insulin concentration between the two groups ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the combination effect of carnitine and other nutrients in beef extract could not be ruled out as suggested by Askew et al (37), which needs to be examined in future studies. For example, it is reported that taurine also decreased body fat (38). Individual muscle contains fiber types in different combinations.…”
Section: Discussionmentioning
confidence: 99%